Evaluation of the phytotherapeutic properties of plants in the prevention and treatment of Gestational Diabetes Mellitus (GDM) (Research, Society and Development, 2025)
Introduction: Gestational Diabetes Mellitus (GDM) is a condition characterized by glucose intolerance with onset or first diagnosis during pregnancy, and is associated with a significant increase in maternal and fetal morbidity and mortality. Given the rising prevalence of GDM and the ongoing search for complementary therapeutic approaches, phytotherapy has emerged as potential alternative in the management of this condition. This study aims to analyze the available scientific evidence on the use of medicinal plants for the adjuvant treatment and prevention of GDM. Methods: An integrative literature review with a qualitative and descriptive approach was conducted. Articles published between January 2010 and March 2025 were included, addressing studies involving humans, animal models, or relevant reviews. After analysis, 20 studies were selected. Results:The analyzed studies involved different types of interventions, including isolated bioactive compounds, plant extracts, and plant-based dietary strategies. Most of the research was conducted using experimental models (animals or in vitro), with only a few clinical trials involving pregnant women. Substances with positive effects on glycemia, insulin resistance, inflammation, and perinatal outcomes were identified, such as: ginger (Zingiber officinale), hibiscus (Hibiscus rosa-sinensis), and curcumin (Curcuma longa). Conclusion:Current literature suggests that certain medicinal plants and phytotherapeutic compounds show potential as adjuvants in the treatment and prevention of GDM, with positive effects on glycemic control and reduction of oxidative stress. However, due to the predominance of preclinical studies and the lack of standardization in interventions, rigorous clinical trials are needed to evaluate the safety and efficacy of these substances in the maternal-fetal context.